THE INFLUENCE OF JOB SATISFACTION AND WORK MORALE ON EMPLOYEE PRODUCTIVITY AT PT. PEGADAIAN PALEMBANG BRANCH OFFICE - Pransiska, Tiara; Akila, Akila; Kurbani, Adie (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine the effect of job satisfaction and morale on employee productivity at PT Pegadaian Palembang Branch Office. The population in this study were all 63 employees, the sample in this study was the same as the population of 63 people using saturated samples. The results of shows that there is a considerable and significant influence of Job Satisfaction and Work Morale on Employee Productivity of PT Pegadaian Palembang Branch Office. The F test obtained that there is a significant influence between the Job Satisfaction and Work Morale simultaneously on Employee Productivity at PT Pegadaian Palembang Branch. Keywords: Job Satisfaction; Work Morale; Employee Productivity